Antifungal curcumin induces reactive oxygen species and triggers an early apoptosis but prevents hyphae development by targeting the global repressor TUP1 in Candida albicans. Issue 6 (24th September 2010) - Sharma, Monika; Manoharlal, Raman; Puri, Nidhi; Prasad, Rajendra
Abstract : In the present study, we have investigated the antifungal effects of a natural polyphenol, CUR (curcumin), against albicans and non- albicans species of Candida and have shown its ability to inhibit the growth of all the tested strains. The inhibitory effects of CUR were independent of the status of the multidrug efflux pump proteins belonging to either ABC transporter (ATP-binding cassette transporter) or MFS (major facilitator) superfamilies of transporters. By using a systemic murine model of infection, we established that CUR and piperine, when administered together, caused a significant fungal load reduction (1.4log10 ) in kidneys of Swiss mice. Additionally, CUR raised the levels of ROS (reactive oxygen species), which, as revealed by annexin V–FITC labelling, triggered early apoptosis in Candida cells. Coincident with the raised ROS levels, mRNAs of tested oxidative stress-related genes [ CAP1 ( Candida albicans AP-1), CaIPF7817 (putative NADH-dependent flavin oxidoreductase), SOD2 (superoxide dismutase 2), GRP2 (NADPH-dependent methyl glyoxal reductase) and CAT1 (catalase 1)] were also elevated. The growth inhibitory effects of CUR could be reversed by the addition of natural and synthetic antioxidants. Notably, independent of ROS status, polyphenol CUR prevented hyphae development in both liquid and solid hypha-inducing media by targeting the global suppressor TUP1 (thymidine uptake 1). Taken together, our results provide the first evidence that CUR acts as an antifungal agent, via generation of oxidative stress, and inhibits hyphae development by targeting TUP1 .